2020
DOI: 10.1101/2020.07.23.20161042
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Overweight/obesity as the potentially most important lifestyle factor associated with signs of pneumonia in COVID-19

Abstract: Objective The occurrence of pneumonia separates severe cases of COVID-19 from the majority of cases with mild disease. However, the factors determining whether or not pneumonia develops remain to be fully uncovered. We therefore explored the associations of several lifestyle factors with signs of pneumonia in COVID-19. Methods Between May and July 2020, we conducted an online survey of adults in Germany who had recently gone through COVID-19, predominantly as outpatients (n=201). Of these, 165 had a PCR-based… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
5
3
0
1
Order By: Relevance
“…In this study, the sex distribution was not too different and it was in line with the studies done in China [19,29]. The recent study reported that (14.8%) of patients were the older age and it seemed to be consistent with the nding obtained in the China study (12.3%) [19] and lower than the studies conducted in the USA (28.3%) [30] and Germany (26.7%) [31]. More than one-fourth of the patients (26.2%) were overweight or obese in this study and this result was lower than the ndings of studies done in Thailand (32.9%) [32], Germany (38.2%) [31], and China (47.5%) [33].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, the sex distribution was not too different and it was in line with the studies done in China [19,29]. The recent study reported that (14.8%) of patients were the older age and it seemed to be consistent with the nding obtained in the China study (12.3%) [19] and lower than the studies conducted in the USA (28.3%) [30] and Germany (26.7%) [31]. More than one-fourth of the patients (26.2%) were overweight or obese in this study and this result was lower than the ndings of studies done in Thailand (32.9%) [32], Germany (38.2%) [31], and China (47.5%) [33].…”
Section: Discussionsupporting
confidence: 90%
“…Over 2012 to 2017, most of the admitted patients with NCDs were middle and older aged population with the median and interquartile range of 39 years and (51.6%) of those were males [38]. In the current study, the most common comorbidities were hypertension and diabetes mellitus and these results supported the ndings of the earlier studies conducted in hospitalized COVID-19 patients [19,30,31,34,36].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Leptin is a hormone secreted by adipocytes in proportion to obesity, a risk factor for severe acute COVID-19 (20), and may contributes to immune dysregulation during acute COVID-19 (21, 22). In our patient population with post-COVID-19 syndrome, we found leptin was inversely related to FVC, however, it is not clear if this simply reflects underlying obesity, a known cause for reduced FVC, or if it represents ongoing immune dysregulation (or both), and requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…This survey was part of the ongoing, prospective, online cohort study Life&Covid that is being conducted in Germany since May 2020. The study design has been described previously (6). In brief, the study mainly aimed at investigating the influence of lifestyle factors on the course of acute COVID-19.…”
Section: Methodsmentioning
confidence: 99%